IZM-5 crystallized solid and method for preparing same

The development of IZM-5, a crystalline solid using zinc and tin, addresses the limitations of existing materials by providing a cost-effective and non-toxic alternative with a unique crystal structure suitable for adsorption and catalysis applications.

JP7653376B2Active Publication Date: 2025-03-28IFP ENERGIES NOUVELLES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021577375
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-16
Publication Date
2025-03-28
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

Existing microporous crystalline materials often rely on rare, expensive, or toxic metals, limiting their widespread application in industries such as petroleum and catalysis.

Method used

A new crystalline solid, IZM-5, is developed using zinc and tin as structural elements, with a specific X-ray diffraction pattern, and is synthesized through a method involving the mixing of tin, zinc, sulfur, and a nitrogenous organic compound, followed by heat treatment.

Benefits of technology

IZM-5 exhibits a unique crystal structure and X-ray diffraction pattern, offering potential applications as an adsorbent or molecular sieve, while avoiding the use of rare or toxic metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653376000004
    Figure 0007653376000004
  • Figure 0007653376000005
    Figure 0007653376000005
  • Figure 0007653376000001
    Figure 0007653376000001
Patent Text Reader

Abstract

The present invention relates to a compound having the general formula: Sn, designated IZM-5, expressed in terms of moles, on an anhydrous basis, and having the following general formula: a Zn b S8 (wherein R represents at least one nitrogenous organic species; S represents sulfur, "a" is the molar amount of tin, denoted as Sn, between 0.1 and 5; "b" is the molar amount of zinc, denoted as Zn, between 0.2 and 8; and "c" is the molar amount of nitrogenous organic species R between 0 and 4).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a new crystalline solid based on metal sulfides, hereinafter referred to as IZM-5, as well as to a process for preparing said solid. [Background technology]

[0002] Crystalline microporous materials, such as zeolites or silicoaluminophosphates, are solids that are widely used in the petroleum industry as catalysts, catalyst supports, adsorbents or separation agents. Although many microporous crystalline structures of various compositions have been discovered, the refining and petrochemical industries and catalytic processes in general are constantly searching for new crystalline structures that exhibit specific properties for applications such as gas purification or separation, conversion of carbon-based entities, etc.

[0003] Zeolites constitute the overwhelming majority of crystalline structures. Among the zeolites synthesized over the last 40 years, a certain number of solids have made it possible to achieve considerable progress in the field of adsorption and catalysis. Among these, mention may be made of Y zeolites (US Pat. No. 5,393,311) and ZSM-5 zeolites (US Pat. No. 5,393,311). The number of new molecular sieves, which encompass zeolites and which are synthesized each year, is constantly increasing. For a more complete description of the different molecular sieves that have been discovered, it may be useful to consult the following references: Molecular Sieves, Vol. 11, No. 1, pp. 1171-1175, 1997.

[0004] Among all these microporous crystalline structures, P. Feng et al. (Non-Patent Document 2) discovered the first material of this type based on sulfides of tetravalent metal structural elements (gallium, tin and germanium) and optionally trivalent metal structural elements (indium), which was named UCR-20 and referenced by the RWY structural code in the "Atlas of Zeolite Framework Types".

[0005] Since then, other crystalline sulfide materials have been claimed in the literature (Non-Patent Document 3), containing structural elements based on trivalent metals (ICF-21, ICF-22, ICF-24, ICF-25 and ICF-27), trivalent and tetravalent metals (ICF-5 and ICF-17) and more recently trivalent and divalent structural elements (Non-Patent Documents 4 and 5).

[0006] However, the metals used in the prior art contain rare and / or expensive and / or toxic structural elements, such as Ga, Ge, In, and even Cd.

[0007] The present invention proposes to provide new specific crystalline solids which contain zinc and tin as structural elements and which exhibit specific X-ray diffraction patterns. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] U.S. Patent No. 3,130,007 [Patent Document 2] U.S. Pat. No. 3,702,886 [Non-patent literature]

[0009] [Non-Patent Document 1] Ch. Baerlocher, LB McCusker and DH Olson, "Atlas of Zeolite Framework Types", 6th revised edition, 2007, Elsevier [Non-Patent Document 2] P. Feng et al., Science, 2002, vol. 298, p2366 [Non-Patent Document 3] P. Feng, Nature, 2003, volume 426, p.428 [Non-Patent Document 4] S. Dehnen et al., Inorg. Chem., 2009, Vol. 48, p. 1689 [Non-Patent Document 5] P. Feng et al., J. Am. Chem. Soc., 2015, Volume 137, p.6184 Summary of the Invention [Means for solving the problem]

[0010] (Subject of the Invention) The subject of the present invention is a compound having the following general formula, expressed in terms of moles, on an anhydrous basis: Sn a Zinc b S8:cR During the ceremony: R represents at least one nitrogenous entity; S is sulfur; "a" is the molar amount of tin, expressed as Sn, from 0.1 to 5; "b" is the molar amount of zinc, expressed as Zn, from 0.2 to 8; "c" is the molar amount of nitrogenous organism R, 0-4 The compound is a crystalline solid having a chemical composition defined by:

[0011] Preferably, "c" is 0.2 to 4.

[0012] Preferably, the solid has an X-ray diffraction pattern which includes at least the lines listed in the table below.

[0013] [Table 1] In the table, VSt = very strong; St = strong; m = medium; w = weak

[0014] Preferably, “a” is 1-4.

[0015] Preferably, "b" is 0.2 to 2.

[0016] Preferably, “c” is 0.5 to 3.

[0017] Preferably, R is an organic compound containing at least two nitrogen atoms.

[0018] More preferentially, R is 1,3-bis(4-piperidinyl)propane.

[0019] Another subject of the invention is a method for preparing a crystalline solid according to the invention, comprising the following steps: i) mixing at least one source of tin, represented by Sn, at least one source of zinc, represented by Zn, at least one source of sulfur, represented by S, and at least one nitrogenous organic compound, represented by R, to obtain a precursor gel; ii) heat treatment of the precursor gel obtained at the end of step i) at a temperature between 120° C. and 250° C. for a period between 2 and 21 days. The present invention relates to a method comprising the steps of:

[0020] Preferably, the mixture of step i) has the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20 Includes.

[0021] Preferably, the mixture of step i) also comprises at least one solvent, designated SOLV, which comprises at least one aqueous compound, designated A, and at least one organic compound, designated O, said mixture having the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20; SOLV / (Sn+Zn): 10-1000; A / O: 0.01 to 10 Contains:

[0022] Preferably, the source of tin is tin acetate Sn(CH3CO2)4, tin tert-butoxide Sn(OC(CH3)3)4, tin tetrachloride SnCl4, tin bis(acetylacetonate) dichloride (CH3COCH=C-(O - )CH3)2SnCl2, tin oxide SnO2, and tin (Sn) in metallic form.

[0023] Preferably, the source of zinc is selected from zinc chloride ZnCl2, zinc acetate Zn(CH3CO2)2, zinc sulfate ZnSO4, zinc nitrate Zn(NO3)2, zinc oxide ZnO, zinc Zn in metallic form.

[0024] Preferably, the source of sulfur is selected from elemental sulfur S or S8, sodium sulfide Na2S, potassium sulfide K2S, lithium sulfide Li2S, ammonium sulfide S(NH4)2, dimethyl disulfide CH3SSCH3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Description of the drawings Other characteristics and advantages of the method according to the invention will become apparent from the following description of a non-limiting exemplary embodiment, with reference to the attached drawings, which are described below.

[0026] FIG. 1 shows the chemical formulae of examples of organic compounds used as structuring agents in the synthesis method according to the invention.

[0027] Figure 2 shows the X-ray diffraction (XRD) pattern of the metal sulfide-based crystalline IZM-5 solid obtained according to Example 1. The x-axis shows the values ​​of the angle 2 theta (2θ) in degrees and the y-axis shows the relative intensity Irel, which is given in relation to a scale of relative intensity where a value of 100 is assigned to the most intense line of the x-ray diffraction pattern.

[0028] Description of the Invention The subject of the present invention is a new solid, called IZM-5, which exhibits a new crystal structure, expressed in terms of moles, on an anhydrous basis, of the following general formula: Sn a Zinc b S8:cR During the ceremony: R represents at least one nitrogenous organism; S is sulfur; "a" is the molar amount of tin, expressed as Sn, from 0.1 to 5; "b" is the molar amount of zinc, expressed as Zn, from 0.2 to 8; "c" is the molar amount of nitrogenous organism R, 0-4 It has a chemical composition defined by:

[0029] The crystalline solid IZM-5 according to the invention has an X-ray diffraction pattern which advantageously contains at least the lines listed in Table 2 below. This new crystalline solid IZM-5 has a new crystal structure which contains very specific lines.

[0030] The diffraction pattern is obtained by radio-crystallographic analysis on a diffractometer using conventional powder techniques with copper Kα1 radiation (λ=1.5406 Å). Based on the positions of the diffraction peaks, expressed by the angle 2θ, the interlattice spacings d hkl is calculated by Bragg's law. d hkl The error Δ(d hkl The measurement of θ is calculated as a function of the absolute error Δ(2θ) assigned to the measurement of 2θ by Bragg's law. An absolute error Δ(2θ) equal to ±0.02° is generally accepted. hkl The relative intensity I assigned to each value of rel are measured by the height of the corresponding diffraction peak. The X-ray diffraction pattern of the IZM-5 crystalline solid according to the invention is given in Table 2 below. hkl Contains at least a line at the value of d hkl In the column, the average interstitial distance is given in angstroms (Å). Each of these values ​​is subject to a measurement error Δ(d hkl ) ±0.6 Å to ±0.01 Å.

[0031] [Table 2]

[0032] In the table, VSt=very strong; St=strong; m=medium; w=weak.

[0033] Relative Intensity I rel are given on a relative intensity scale in which a value of 100 is assigned to the most intense line of the X-ray diffraction pattern: w<10; 10≦m<15; 15≦St<50; VSt≧50.

[0034] The solid IZM-5 has the following general formula, expressed in terms of moles, on an anhydrous basis: Sn a Zinc b S8:cR During the ceremony: "a" is the relative molar amount of Sn of 0.1 to 5, preferably 1 to 4; "b" is the relative molar amount of Zn of 0.2 to 8, preferably 0.2 to 2; "c" is the molar amount of nitrogenous organism R between 0 and 4, preferably between 0.2 and 4, more preferentially between 0.5 and 3; It has a chemical composition defined by:

[0035] The subject of the present invention is a method for preparing the crystalline solid IZM-5, comprising at least the following steps: i) mixing at least one source of tin, denoted Sn, at least one source of zinc, denoted Zn, at least one source of sulfur, denoted S, at least one nitrogenous organic compound, also called structuring agent, denoted R, preferably 1,3-bis(4-piperidinyl)propane, and optionally at least one solvent, denoted SOLV, comprising at least one aqueous compound (denoted A) and / or at least one organic compound (denoted O), to obtain a precursor gel, said mixture preferentially having the following molar composition: Sn / Zn: at least 0.1, preferably at least 1, more preferably 2-200; S / (Sn+Zn): 0.1-20, preferably 1-10; R / (Sn+Zn): 0.1 to 20, preferably 1 to 10; SOLV / (Sn+Zn): 0 to 1000, preferably 10 to 500, preferably 10 to 400, more preferably 20 to 400; A / O: 0.01 to 10, preferably 0.1 to 8, preferably 0.2 to 5; exhibiting a process; ii) heat treatment of the precursor gel obtained at the end of step i) at a temperature between 120° C. and 250° C. for a period between 2 and 21 days; There are also methods that include

[0036] Preferably, the mixture obtained in step i) has the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20 Includes.

[0037] Preferably, the mixture of step i) also comprises a solvent designated SOLV, said mixture having the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20; SOLV / (Sn+Zn): 10-1000 Includes.

[0038] According to the method according to the invention, R is a nitrogenous organic compound having at least one nitrogen atom, preferably R contains two nitrogen atoms, said compound being incorporated as organic structuring agent in the reaction mixture for carrying out step i). Preferentially, R is the nitrogenous compound 1,3-bis(4-piperidinyl)propane. Said nitrogenous organic compound used as structuring agent for the crystalline solid IZM-5 can be synthesized by any method known to the person skilled in the art.

[0039] According to the process according to the invention, at least one source of tin is used in the reaction mixture of step i) and can be any compound that contains elemental tin and is capable of releasing this element in an active form into the mixture. The source of tin is preferably selected from the group consisting of tin acetate Sn(CH3CO2)4, tin tert-butoxide Sn(OC(CH3)3)4, tin tetrachloride SnCl4, tin bis(acetylacetonate) dichloride (CH3COCH=C-(O - )CH3)2SnCl2, tin oxide SnO2, the metallic form of tin.

[0040] According to the process according to the invention, the at least one source of zinc is used in the reaction mixture of step i) and can be any compound that contains elemental zinc and is capable of releasing this element in an active form into the mixture. The source of zinc is preferably zinc chloride ZnCl2, zinc acetate Zn(CH3CO2)2, zinc sulfate ZnSO4, zinc nitrate Zn(NO3)2, zinc oxide ZnO, zinc Zn in metallic form.

[0041] According to the method according to the invention, at least one source of sulfur is used in the reaction mixture of step i) and can be any compound that contains elemental sulfur and is capable of releasing this element in active form into the mixture. The source of sulfur is preferably solid or liquid under standard temperature and pressure conditions. The source of sulfur is preferably elemental sulfur S or S8, sodium sulfide Na2S, potassium sulfide K2S, lithium sulfide Li2S, ammonium sulfide S(NH4)2, dimethyl disulfide CH3SSCH3.

[0042] According to the process according to the invention, at least one optional solvent is used in the reaction mixture of step i) and can be an aqueous and / or organic compound. According to one variant, the solvent consists of an aqueous compound and an organic compound. The aqueous compound may be selected from water H2O and the organic compound may be selected from compounds that are liquid under standard temperature and pressure conditions and are of the alcohol (preferably ethanol, isopropanol), diol (preferably ethylene glycol, propylene glycol), triol (preferably glycerol or propane-1,2,3-triol), organosulfur (preferably dimethylsulfoxide or DMSO) or organonitrogen compound (preferably dimethylformamide or DMF) type.

[0043] According to another variant, no additional solvent is used in the process for preparing the crystalline solid IZM-5, which is a nitrogenous organic compound designated R when it is in liquid form under standard conditions of temperature and pressure allowing the solubilization of the metal precursor and the sulfur-bearing precursor.

[0044] Step i) of the process according to the invention consists in preparing a reaction mixture, called gel, containing at least one source of tin, at least one source of zinc, at least one source of sulfur, at least one nitrogenous organic substance R, and optionally a solvent, the amounts of said reactants being adjusted as indicated above so as to give on this gel a composition which allows its crystallization as a crystalline solid IZM-5 in its crude synthetic form.

[0045] The mixing step i) is carried out with stirring at low or high shear rates, preferably by any system known to the skilled artisan, for a period of time preferably not less than 15 minutes, until a homogeneous mixture is obtained. At the end of step i), a homogeneous precursor gel is obtained.

[0046] It may be advantageous to add seeds to the reaction mixture during said step i) of the method according to the invention in order to reduce the time required for the formation of crystals and / or the total crystallization time. The seeds also suppress impurities and promote the formation of crystalline solid IZM-5. Such seeds include crystalline solids, especially solid IZM-5 crystals. The crystal seeds are generally added in a proportion of 0.01% to 10% by weight relative to the total weight of the tin and zinc precursors used in the reaction mixture.

[0047] It may be advantageous to carry out an ageing of the reaction mixture during step i) followed by a heat treatment ii) of the process according to the invention in order to suppress impurities and control the size of the crystals of the crystalline solid IZM-5. Said ageing also promotes the formation of the crystalline solid IZM-5 at the expense of impurities. The ageing of the reaction mixture during step i) of the process according to the invention may be carried out at ambient temperature or at a temperature between 20 and 100° C., with or without stirring, for a period advantageously between 30 min and 48 h.

[0048] According to step ii) of the method according to the invention, the precursor gel obtained at the end of step i) is subjected to a heat treatment, preferentially at a temperature between 120°C and 250°C, for a period between 2 and 21 days, until a crystalline solid IZM-5 is formed.

[0049] The gel is advantageously placed under autogenous reaction pressure, optionally with the addition of a gas, such as nitrogen, at a temperature between 120°C and 250°C, preferably between 140°C and 210°C, until crystals of solid IZM-5 are formed in its crude synthetic form.

[0050] The time required to obtain crystallization generally ranges from one day to several months depending on the composition of the reactants in the gel, the stirring and reaction temperature. Preferably, the crystallization time ranges from 2 to 21 days, preferably from 5 to 15 days.

[0051] The reaction is generally carried out with or without stirring, preferably with stirring. Stirring systems which may be used are any systems known to those skilled in the art, such as counter-bladed pitched blades, stirred turbomixers or Archimedes screws.

[0052] At the end of the reaction, after carrying out said step ii) of the preparation process according to the invention, the solid phase constituted by IZM-5 solids is preferably filtered, washed and then dried. Preferably, the washing step will be carried out with ethanol or the solvent used for the synthesis. The drying treatment is generally carried out at a temperature between 20°C and 150°C, preferably between 60°C and 100°C, for a period of between 5 hours and 24 hours.

[0053] At the end of the drying step, the resulting IZM-5 solid has an X-ray diffraction pattern that includes at least the lines listed in Table 1.

[0054] After step ii), optionally after the abovementioned filtering, washing and drying steps, a step of extraction of the organism R to free the microporosity may be carried out by any method known to the skilled artisan. Preferably, this step may be carried out using a heat treatment at 100°C to 1000°C under air, oxygen, hydrogen, H2S or an inert gas, such as N2, either alone or as a mixture. This extraction may be carried out using an entity, such as NH4 + The oxidation can also be achieved by ion exchange with alkali, alkaline earth metals or any metal cation.

[0055] After extraction of the organism R, the crystalline solid IZM-5 according to the invention can be used as an adsorbent, for example for pollution control, or as a molecular sieve for separations.

[0056] (Example) The present invention is illustrated by the following examples, which are not limiting in any way.

[0057] Example 1: Preparation of IZM-5 solids according to the present invention 0.228 g of tin dioxide (SnO2, 99% purity by weight, Sigma-Aldrich) was mixed with 0.146 g of zinc nitrate (Zn(NO3)2·6H2O, 99% purity by weight, Alfa Aesar). Then, 0.277 g of sulfur (S, 99.98% purity by weight, Aldrich) and 2.001 g of 1,3-bis(4-piperidyl)propane (compound R, 97% purity by weight, Aldrich) were added to the previous mixture. At the end, 11.2 mL of ethylene glycol (99.8% purity by weight, VWR) and 3.7 mL of deionized water were incorporated and stirring (250 rpm) of the synthesis gel was maintained for 30 min. The precursor gel was then transferred to an autoclave after homogenization. The autoclave was closed and then heated under static conditions at 190 °C for 12 days. The resulting crystalline product is filtered, washed with ethanol, and then dried at 100° C. overnight. The crude solid synthesis product was analyzed by X-ray diffraction and confirmed to consist of solid IZM-5. The resulting diffraction pattern for the crude IZM-5 synthesis solid is given in FIG. 2. The product has a Sn / Zn molar ratio of 5.7 as determined by ICP-MS. Elemental analysis gives the following molar composition: Sn 3.4 Zinc 0.6 S8:1.1R Example 2: Preparation of IZM-5 solids according to the present invention 0.293 g of tin dioxide (SnO2, 99% purity by weight, Sigma-Aldrich) was mixed with 0.141 g of zinc nitrate (Zn(NO3)2·6H2O, 99% purity by weight, Alfa Aesar). Then, 0.267 g of sulfur (99.98% purity by weight, Aldrich) and 2.002 g of 1,3-bis(4-piperidyl)propane (compound R, 97% purity by weight, Aldrich) were added to the previous mixture. At the end, 11.5 mL of ethylene glycol (99.8% purity by weight, VWR) and 3.6 mL of deionized water were incorporated and stirring (250 rpm) of the synthesis gel was maintained for 30 min. The precursor gel was then transferred to an autoclave after homogenization. The autoclave was closed and then heated under static conditions at 190 °C for 12 days. The resulting crystalline product is filtered, washed with ethanol, and then dried at 100° C. overnight. The crude solid synthesis product was analyzed by X-ray diffraction and found to consist of IZM-5 solids, along with traces of SnO. The product has a Sn / Zn molar ratio of 5.8 as determined by ICP-MS. Elemental analysis gives the following molar composition: Sn 3.5 Zinc 0.6 S8:1R.

[0058] Example 3: Preparation of IZM-5 solids according to the present invention 0.240 g of metallic tin (Sn, 99% purity by weight, Sigma-Aldrich) was mixed with 0.144 g of zinc nitrate (Zn(NO3)2·6H2O, 99% purity by weight, Alfa Aesar). Then, 0.276 g of sulfur (S, 99.98% purity by weight, Aldrich) and 2.000 g of 1,3-bis(4-piperidyl)propane (compound R, 97% purity by weight, Aldrich) were added to the previous mixture. At the end, 11.2 mL of ethylene glycol (99.8% purity by weight, VWR) and 3.7 mL of deionized water were incorporated and stirring (250 rpm) of the synthesis gel was maintained for 30 min. The precursor gel was then transferred to an autoclave after homogenization. The autoclave was closed and then heated under static conditions at 190 °C for 12 days. The resulting crystalline product is filtered, washed with ethanol, and then dried at 100° C. overnight. The crude solid synthesis product was analyzed by X-ray diffraction and found to consist of IZM-5 solids, with traces of Sn. The product has a Sn / Zn molar ratio of 5.9, as determined by ICP-MS. Elemental analysis gives the following molar composition: Sn 3.7 Zinc 0.6 S8: 0.95R. [Brief description of the drawings]

[0059] [Figure 1] 1 shows the chemical formulas of examples of organic compounds used as structuring agents in the synthesis method according to the invention. [Diagram 2] 1 shows an X-ray diffraction (XRD) pattern of the metal sulfide-based crystalline IZM-5 solid obtained according to Example 1.

Claims

1. Expressed in terms of moles on an anhydrous basis and having the general formula: Sn a Zn b S 8 :cR During the ceremony: R is 1,3-bis(4-piperidinyl)propane; S is sulfur; "a" is the molar amount of tin, represented as Sn, from 1 to 4; "b" is the molar amount of zinc, expressed as Zn, from 0.2 to 2; "c" is the molar amount of nitrogenous organism R between 0.2 and 4 A crystalline solid having a chemical composition defined by

2. 2. The crystalline solid of claim 1, wherein the solid exhibits an X-ray diffraction pattern including at least the lines listed in the table below. 【Table 1】 In the table, VSt = very strong; St = strong; m = medium; w = weak

3. 3. The crystalline solid of claim 1 or 2, wherein "c" is from 0.5 to 3.

4. A method for preparing a crystalline solid according to any one of claims 1 to 3, comprising the following steps: i) mixing at least one source of tin, represented by Sn, at least one source of zinc, represented by Zn, at least one source of sulfur, represented by S, and 1,3-bis(4-piperidinyl)propane, represented by R, to obtain a precursor gel; ii) a heat treatment of said precursor gel obtained at the end of step i) at a temperature between 120° C. and 250° C. for a period between 2 and 21 days. A method comprising:

5. The mixture of step i) has the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20 The method of claim 4 , comprising:

6. The mixture of step i) also contains at least one solvent, denoted SOLV, to obtain a precursor gel, said solvent comprising at least one aqueous compound (denoted A) and at least one organic compound (denoted O), said mixture having the following molar composition: Sn / Zn: at least 0.1; S / (Sn+Zn): 0.1-20; R / (Sn+Zn): 0.1-20; SOLV / (Sn+Zn): 10-1000; A / O: 0.01~10 The method of claim 4 , comprising:

7. The source of tin is tin acetate, Sn(CH 3 CO 2 ) 4 , tin tert-butoxide Sn(OC(CH 3 ) 3 ) 4 , Tin tetrachloride SnCl 4 , tin bis(acetylacetonate) dichloride (CH 3 COCH=C-(O - ) CH 3 ) 2 SnCl 2 , tin oxide SnO 2 , tin (Sn) in metallic form.

8. The source of zinc is zinc chloride, ZnCl 2 , zinc acetate Zn(CH 3 CO 2 ) 2 , zinc sulfate ZnSO 4 , zinc nitrate Zn(NO 3 ) 2 8. The method according to claim 4, wherein the zinc oxide is selected from the group consisting of zinc oxide ZnO and zinc in metallic form Zn.

9. The source of sulfur is elemental sulfur S or S 8 , sodium sulfide Na 2 S, potassium sulfide K 2 S, lithium sulfide Li 2 S, ammonium sulfide S (NH 4 ) 2 , dimethyl disulfide CH 3 S.S.C.H. 3 The method according to any one of claims 4 to 8, wherein the method is selected from the group consisting of

Citation Information

Patent Citations

  • ZnS / SnS composite material powder synthesized by utilizing high-pressure solvothermal

    CN104108742A

  • Copper-zinc-tin chalcogenide nanoparticles

    JP2012527401A

  • Method for forming ink

    JP2013214748A

  • Crystalline zeolite y

    US3130007A

  • Crystalline zeolite ZSM-5 and method of preparing the same

    US3702886A